2019
DOI: 10.5539/ijel.v9n5p78
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Pakistani English Newspaper Texts: An Application of Halliday and Hasan’s Model of Cohesion: A Discourse Analysis

Abstract: This article aims to examine the patterns of each type of cohesive device in light of the cohesion model proposed by Halliday and Hasan in 1976. Halliday and Hasan identified five different types of cohesion: reference, substitution, ellipsis, conjunction and lexical cohesion in the text. This study uses the selected weekly articles authored by Cyril Almeida from well-known daily published English Newspaper “The Daily Dawn”. Analysis of text comprises Halliday and Hasan’s cohesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The conjunctions were most common in chapter II or the literature review. They were dominated by additive conjunctions, which meant that most of the text contained extra information without moving the ideas from the last phrase or clause (Afzaal et al, 2019)…”
mentioning
confidence: 99%
“…The conjunctions were most common in chapter II or the literature review. They were dominated by additive conjunctions, which meant that most of the text contained extra information without moving the ideas from the last phrase or clause (Afzaal et al, 2019)…”
mentioning
confidence: 99%
“…She concluded her research that reiteration was most frequently found in the text. Afzaal, Hu, Chishti, and Imran (2019) in their research study on Pakistani English newspapers, apply Halliday and Hassan's model of cohesion. They applied this model to examine all cohesive devices and their regular pattern in the newspaper.…”
Section: 3mentioning
confidence: 99%
“…Levy (2009) and Imran et al (2019) point out that in each language aspect, a suitable technology should apply which helps the students to practice these tools to learn a language properly. According to Hubbard (2008) and Afzaal et al (2019), the crucial component that teachers need to be prepared with for real classrooms. Chapelle (2005) said teaching English programs have emphasized the importance of equipping teachers with the necessary skills and expertise to develop CALL materials.…”
Section: Developmentmentioning
confidence: 99%